The causes of Ireland's unemployment - Newell, Andrew; Symons, J. (Economic & Social Studies, 1990)
We outline a small model of the Irish labour market and use it to explain what has happened over the last 10 years. We conclude that Irish unemployment problems in the 1980s were due to international demand-side factors, such supply-side factors as taxes and unemployment relief, and demographies, in the approximate proportion 4:2:3.
Keywords: Unemployment; Labour market; Ireland